Spatial covariance of herbivorous and predatory guilds of forest canopy arthropods along a latitudinal gradient. (18th August 2020) - Mottl, Ondrej; Fibich, Pavel; Klimes, Petr; Volf, Martin; Tropek, Robert; Anderson‐Teixeira, Kristina; Auga, John; Blair, Thomas; Butterill, Phil; Carscallen, Grace; Gonzalez‐Akre, Erika; Goodman, Aaron; et al.
Abstract: In arthropod community ecology, species richness studies tend to be prioritised over those investigating patterns of abundance. Consequently, the biotic and abiotic drivers of arboreal arthropod abundance are still relatively poorly known. In this cross‐continental study, we employ a theoretical framework in order to examine patterns of covariance among herbivorous and predatory arthropod guilds. Leaf‐chewing and leaf‐mining herbivores, and predatory ants and spiders, were censused on > 1000 trees in nine 0.1 ha forest plots. After controlling for tree size and season, we found no negative pairwise correlations between guild abundances per plot, suggestive of weak signals of both inter‐guild competition and top‐down regulation of herbivores by predators. Inter‐guild interaction strengths did not vary with mean annual temperature, thus opposing the hypothesis that biotic interactions intensify towards the equator. We find evidence for the bottom‐up limitation of arthropod abundances via resources and abiotic factors, rather than for competition and predation. Abstract : We developed a theoretical framework predicting various covariance patterns among herbivorous and predatory guilds. We censused abundances of two herbivore and two predatory guilds on > 1000 trees from nine 0.1‐ha plots at various latitudes and altitudes. Our whole‐forest censuses provide evidence for bottom‐up limitation of arboreal arthropods by resources and abiotic factors, rather than competition and predation.